Original Personalized Reconstruction Method for Certain Large Tumors of the Lower Lip (Not Including Oral Commissures) - Ovidiu Dan Grigorescu; Marius Irimie; Nadinne Roman; Roxana Steliana Miclaus; Maria-Cristina Cîmpeanu; Bogdan-Radu Necula; Christian-Gabriel Strempel; Simona Grigorescu; Marius Alexandru Moga; Dana Gabriela Festila (Medicina)
Background/Objective: Surgical treatment of extensive tumors of the lower lip generates important defects in its structure and functions. Over time, a multitude of reconstruction options for these defects have been imagined. Unfortunately, the majority involve the use of both local and regional flaps, which either lack labial structure or disorganize the oral commissures as nodal oral function points. We set out to design a new reconstruction method that is not burdened by any of the above disadvantages, starting from the necessity to reconstruct large lower lip defects by exclusively using local and/or regional labial flaps belonging only to the healthy upper lip and the remaining structures of the lower lip after surgical tumor removal. In this way, the tissues involved in lower lip reconstruction will have a 100% labial structure and, supplementarily, the remaining oral commissures will not be damaged. Method: This new reconstruction method is based on the original association of WY-plasty to reduce the size of the large primary defect until it becomes congruent with the Abbe–Sabattini cross-lip flap. Results: Applied in a personalized manner, impressive results were obtained in several patients with lip tumors affecting about one-half of the lower lip length and in whom oncological surgical ablation produced defects in more than two-thirds of it. Conclusions: This new method is characterized by functional oral advantages, and can be applied in a personalized way to only certain categories of patients. Other disadvantages are characteristic and specific of Abbe–Sabattini cross-lip flap plasty.